How culturally competent are hospitals in Israel? - Michal Schuster; Irit Elroy; Bruce Rosen (BMC, 2018)
Abstract Background Cultural competence (CC) in health systems is the ability to provide care to patients with different values, beliefs and behaviors, and to match the care to their social, cultural and linguistic needs. In 2011, the Director-General of Israel's Ministry of Health issued a cultural competence directive to health care providers that sought to minimize health inequalities caused by cultural and linguistic gaps. This study assesses the status of organizational CC in Israeli general hospitals in the wake of the 2011 directive. Method Organizational CC was assessed using a 75-item structured questionnaire based on the 2011 directive and on international standards. Data were gathered via interviews conducted between December 2012 and February 2014. 35 of Israel's 36 general hospitals participated in the study, for a response rate of 97%. A composite CC score was calculated for each hospital as the average of the 75 items in the questionnaire. Results The average composite score of all the hospitals was low to moderate (2.3 on a scale of 0-4), the median score was 2.4, and the range of composite scores was large, 0.7-3.2. The interquartile range was [1.94, 2.57]. Hospital CC is positively associated with non-private ownership status and location in the southern or central districts. Still, these differences are not statistically significant and immutable hospital characteristics such as ownership status and location account for only 21% of the inter-hospital variation in CC. This suggests that hospital leaders have significant discretion in the priority to be given to CC. Dimensions of CC with relatively low average scores include hospital connections with the community (1.28), staff training on CC (1.35), oral translation (i.e. interpreting) during treatment (1.62), and CC adaptation of human resources recruitment and evaluation (1.64). These areas appear to be particularly in need of improvement. Conclusion The study findings suggest that hospitals and policy-makers can take significant steps to improve CC; these include setting more concrete and measurable implementation guidelines. We conclude with suggestions for policy and practices to improve cultural competence in the health system.